2020
DOI: 10.1017/cem.2020.427
|View full text |Cite
|
Sign up to set email alerts
|

Development of a whiteboard video for managing trauma patients outside a tertiary trauma centre

Abstract: This article describes the process of developing an educational whiteboard video for community trauma management and transport. Whiteboard videos have become widely used as educational resources for various medical subject matters. These short videos package information concisely through real-time illustration with an accompanying narration. Based on a needs assessment we created a free open access educational resource for community trauma management and transport. A group of interdisciplinary trauma providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Engagement from WB may be related to the qualities of the format, in that they guide, are simple by nature and are interactive. [24][25][26] This "first-person experience involvement" encourages knowledge construction. 27 A small non-validated study suggested a 15% increase in the retention of information and a 66% increase in the number of participants willing to share the information following the utilisation of WB animation.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement from WB may be related to the qualities of the format, in that they guide, are simple by nature and are interactive. [24][25][26] This "first-person experience involvement" encourages knowledge construction. 27 A small non-validated study suggested a 15% increase in the retention of information and a 66% increase in the number of participants willing to share the information following the utilisation of WB animation.…”
Section: Discussionmentioning
confidence: 99%